Reconstruction Material Sumping Accesories with Customization Design (Joni Permana Artwork) - Rika Nugraha; Elin Herlina (Balong International Journal of Design, 2018)
Sumping is a type of jewelry worn on the ears. It is usually carved in the shape resemble with wings of a bird or swirls strands of leaves. Way of wearing sumping is tucking the earlobe on the curved hole sumping. It is found in Indonesia, especifically in Javanese culture and traditional dress, worn as attributes on Thailand clothing dancers. Sumping is one of the attributes of the completeness of the clothing dance like Java serimpi dance and puppet people. Works of art in the form of Sumping has been reconstructed by Joni Permana as costum art designer, Sumping which is now no longer used as the complement of traditional dance, through display design costumized Sumping has a point of interest in any performance. The reconstruction is done by not changing the form as well as its usefulness, but sumping effort of reconstruction is done so that the use of sumping maintained through a culture of innovation. Sumping has high cultural value as cultural products as well as aesthetic value in its works so that cultural heritage still has continuous existence.Keywords—.  Reconstruction, Sumping, Customization